Unusual Cause of Cardiac Compression in a Trauma Patient: Cystic Thymoma - Sahin Bozok; Özcan YavaŞİ; Gokhan Ilhan; Ali Gurbuz (Western Journal of Emergency Medicine, 2012)
N/a images in emergency medicine